mRNA Differential Display Visualized by Silver Staining Tested on Gene Expression in Resurrection Plant Boea hygrometrica1 - Deng, X.; Hu, Z.A.; Wang, H.X.
A new protocol for nonradioactive mRNA differential display with high sensitivity visualized by DNA silver staining is presented. The protocol has been tested on total RNA of resurrection plantBoea hygrometrica to identify genes differentially expressed in dehydrated leaves compared to fresh and re-hydrated leaves. Total RNAs were reversely transcribed using three anchored oligo-dT primers. PCR amplification of relative cDNAs was carried out in combination with eight arbitrary primers. Urea-denatured polyacrylamide gel electrophoresis is used to separate amplified products of various molecular weights. Bands of amplified transcripts were resolved by silver staining, and the sensitivity was high enough to detect the tiny differences in DNA electrophoresis pattern. Several specific transcripts were successfully identified by this procedure, and one of them was cloned and sequenced.